Cationic exchange in nanosized ZnFe₂O₄ spinel revealed by experimental and simulated near-edge absorption structure - Stewart, Silvana Jacqueline (2007)
The nonequilibrium cation site occupancy in nanosized zinc ferrites ( ∼ 6 – 13 nm ) with different degree of inversion ( ∼ 0.2 to 0.4) was investigated using Fe and Zn K -edge x-ray absorption near edge spectroscopy (XANES) and extended x-ray absorption fine structure, and magnetic measurements. The very good agreement between experimental and ab initio calculations on the Zn K -edge XANES region clearly shows the large Zn²⁺ ( A ) → Zn²⁺ [ B ] transference that takes place in addition to the well-identified Fe³⁺ [ B ] → Fe³⁺ ( A ) one, without altering the long-range structural order. XANES spectra features as a function of the spinel inversion were shown to depend on the configuration of the ligand shells surrounding the absorbing atom. This XANES approach provides a direct way to sense cationic inversion in these Zn-containing spinel ferrites. We also demonstrated that a mechanical crystallization takes place on nanocrystalline spinel that causes an increase of both grain and magnetic sizes and, simultaneously, generates a significant augment of the inversion.